Payroll Loans and the Vulnerability of the Elderly in Brazil: Risks, Over-Indebtedness, and Legal Protection (CIPEEX, 2025)
Payroll loans initially offer advantages to retirees and pensioners, such as reduced interest rates and ease of approval due to automatic installment deductions. However, this credit modality also poses risks for this demographic, who often face challenges in understanding contractual terms and financial implications. Brazilian legislation, including the Elderly Statute (Law No. 10.741/2003), aims to protect these consumers from abusive practices, but the complexity of contracts and lack of clarity in information leave many elderly vulnerable to over-indebtedness and fraud. This study, supported by sociological and doctrinal concepts, analyzes the risks and impacts of payroll loans on the quality of life of the elderly, highlighting the need for greater transparency and financial education. It concludes that enhanced regulatory protection and educational initiatives are essential to ensure that payroll loans serve the interests of the elderly ethically and responsibly.
Keywords: Payroll loans; Over-indebtedness; Financial vulnerability; Legislation; Consumer protection